Impact of climate change and infectious diseases: Implications for healthcare providers in the UK - Christina Petridou; Amy Belfield (Future Healthcare Journal)
Rising temperatures and changes in precipitation and humidity may affect the geographic ranges and habitats of pathogens and their animal hosts, and directly influence the reproduction, replication and transmissibility of certain pathogens and their vectors. These changes can lead to novel diseases presenting in new places, and a change in the seasonality of vector-borne diseases such as malaria, dengue and Lyme disease. Here we discuss the changing epidemiology of vector-borne diseases in the UK and abroad, and give some case examples. We will also discuss the importance of, and how to take, a detailed travel history and the impact of climate change on travel-associated infections.